Ongoing Controversy over SUPPORT - Kaebnick, Gregory E. (The Hastings Center report, 2015)
It has been a couple of years now since debate erupted over the study known as the Surfactant, Positive Pressure, and Oxygenation Randomized Trial, which sought to gauge the risks and benefits of different blood oxygen levels currently targeted in the care of premature infants. Both articles in this issue of the Hastings Center Report try to take the debate to a new level, but as expressed in the title of one of three commentaries on the articles, the controversy shows no signs of abating.